Use of low intensity ultrasound in fat back from pigs with different genetic background - Ventanas S.; Ventanas J.; Jurado A.; Cácel J.A.; Niñoles L. (5. International Symposium on the Mediterranean Pig, 2007)
In this work, the use of low-intensity ultrasound on back fat as an objective and non-destructive analytical technique to differentiate between back fats from Iberian pigs (Ib) and from Iberian x Duroc (IbxD) crossbreed pigs, was studied. The ultrasonic velocity decreased as the temperature during the assay increased (from 0 to 25°C) in all the batches. This fact is caused by the melting of the fat with increasing temperatures resulting in an increase in the liquid content of the system. It is generally recognised that the ultrasonic velocity is lower in liquid than in solid fat. Measurements of ultrasonic velocity were significantly lower in back fat from the Ib batch (1594 m/s) than in the IbxD batch counterpart (1600 m/s). These results are probably due to the differences in fatty acid composition between the batches. Back fat from the Ib batch shows significantly higher percentages of oleic acid and monounsaturated fatty acids than that from the IbxD batches. Therefore, back fat from Ib was more fluid than IbxD back fat, which involves a decrease in ultrasonic velocity in the former. In conclusion, these results show that the measurement of ultrasonic velocity in fat back could be used to differentiate between pure Iberian pigs and Iberian x Duroc crossbreed pigs.
5. International Symposium on the Mediterranean Pig, 2004/09/16-19, Tarbes (France)